FAKTOR – FAKTOR YANG MEMENGARUHI KEPUTUSAN INVESTASI PADA GENERASI MILENIAL - Hana, Alfiyah; Ambardi, Ambardi; Novida, Irma (Politeknik Negeri Ambon, 2024)
This research aims to assess the influence of social media characteristics, risk perception, and financial literacy on investment decisions in the capital market among millennials in Tangerang. This research uses quantitative methods. The data collection approach uses a questionnaire survey instrument. Participants in this research are individuals who carry out transactions in the capital market, sometimes referred to as respondents or consumers. A total of 106 respondents were involved in this research, selected using a simple random sampling technique. The analytical methods used include Descriptive Analysis and Partial Least Square (PLS) Analysis. Research findings show that social media, Risk perception, and financial literacy have a big influence on investment decisions of the millennial generation in the Tangerang capital market.